Transition metal diphenolate and dithiophenolate complexes as synthetic analogues of the active sites of nickel superoxide dismutase and galactose oxidase - Marshall, George (2016)
This thesis describes the synthesis of diphenolate and dithiophenolate complexes of ZnII, NiII and CuII that derive inspiration from the natures of the active sites of the nickel-containing superoxide dismutase (NiSOD) and the copper-containing galactose oxidase (GO). Chapter One introduces the roles of transition metals in biology. The structures of the active sites of NiSOD and GO are described, together with a discussion of the proposed mechanisms of their action. A brief review of the coordination chemistry relevant to the chemistry of the actives sites of NiSOD and GO is presented and the aims of the research described in this thesis are set out. Chapter Two describes the syntheses and structural characterisations of a series of pentacoordinate ZnII, NiII and CuII diphenolate complexes MRLoNMe (M= Zn, Ni, Cu; R = Cl, Br, Nap, Ph, PhMe, PhOMe, tBu/Br, tBu/Ph, tBu/PhMe, tBu/PhOMe; page xiii) that differ in the natures of the substituents at the 3- and 5-positions of the phenolate rings within the ligand backbone. X-ray crystallographic studies on the ZnII, NiII and CuII complexes, and room temperature and frozen solution EPR spectroscopic experiments on the CuII complexes provide insight into the influence of the 3- and 5- substitution on the coordination geometries. The changes in substitution at the 3 position of the phenolate rings in MRLoNMe (M= Zn, Ni, Cu; R = tBu/Ph, tBu/PhMe, tBu/PhOMe) have significantly less influence on the geometry about the metal centre when compared to complexes that have substitutions that vary at the 3 and 5 positions in MRLoNMe (M= Zn, Ni, Cu; R = Ph, PhMe, PhOMe). DFT calculations provide a qualitative description of the electronic structures of these complexes, suggesting an increase in the metal character within the HOMOs for the NiII complexes relative to those of their ZnII and CuII counterparts. Chapter Three describes the electrochemical characterisations of the complexes synthesised in Chapter Two [MRLoNMe (M= Zn, Ni, Cu; R = Cl, Br, Nap, Ph, PhMe, PhOMe, tBu/Br, tBu/Ph, tBu/PhMe, tBu/PhOMe)]. Cyclic voltammetry demonstrates that MRLoNMe (M= Zn, Cu; R = Cl, Br, Nap, tBu/Br) possess oxidation processes that are not reversible. MRLoNMe (M= Ni; R = Cl, Br, Nap, tBu/Br) possess a reversible oxidation process assigned to the NiIII/NiII redox couple. MRLoNMe (M= Zn, Ni, Cu; R = Ph, PhMe, PhOMe, tBu/Ph, tBu/PhMe, tBu/PhOMe) display multiple oxidation processes, some of which demonstrate electrochemical reversibility, particularly when M = Ni or Cu. UV/Vis and EPR spectroscopic studies on the oxidised species [MRLoNMe]+ (M= Zn, Ni, Cu; R = Ph, PhMe, PhOMe, tBu/Ph, tBu/PhMe, tBu/PhOMe), supported by DFT calculations, suggest that the first oxidation process is significantly more metal based when M = Ni than for M = Cu or Zn and for the generation of [NiRLoNMe]+ is associated with the formation of formal NiIII species. The UV/vis and EPR spectroscopic results also suggest that [NiPhOMeLoNMe]+ exhibits temperature-dependent NiIII-phenolate  NiII-phenoxyl redox tautomerism. The variation of the aromatic substituents systematically decreases the redox potential in the order R = Ph > PhMe > PhOMe, consistent with the relative electron donor properties of each group. Chapter Four examines complexes that incorporate an aromatic, N-donor group pendant to the ligand background. These complexes serve as analogues of the active site of NiSOD. The dithiophenolate and diphenolate complexes NitBuLSPy, NitBuLSPyOMe, NitBuLOPy, NitBuLOPyOMe, and NitBuLOPh are prepared and characterised to examine the effect of different N-donor groups as potential axial donors to the metal centre on the redox properties of each complex. Advanced pulsed ESSEM and HYSCORE EPR spectroscopic studies probe the weak superhyperfine couplings involving the 14N imine donors in [NitBuLSPy]+, and benchmark the spin densities associated with these donors calculated by DFT. These spectroscopically validated DFT calculations show how the distribution of spin density varies between complexes incorporating an N-donor pendant to the ligand backbone and those that do not. Thus, those incorporating an additional N-donor possess spin density that is considerably more localised at the formal NiIII centre than those that do not. Chapter Five discusses the key conclusions of the research described in this thesis and compares and contrasts the chemistry exhibited by ZnII, NiII and CuII diphenolate and dithiophenolate complexes. The structural and electrochemical differences observed upon the introduction of alternative diphenolate substituents in MRLoNMe (M= Zn, Ni, Cu; R = Cl, Br, Nap, Ph, PhMe, PhOMe, tBu/Br, tBu/Ph, tBu/PhMe, tBu/PhOMe) are summarised, together with the importance of the geometric structure of NitBuLSPy in controlling the redox chemistry of this centre. Finally, implications for the chemistry of the active sites of GO and NiSOD are discussed.